Community perceptions of intimate partner violence - a qualitative study from urban Tanzania - Emmelin Maria; Lugina Helen I; Nyström Lennarth; Laisser Rose M (BMC, 2011)
Abstract Background Intimate partner violence against women is a prevailing public health problem in Tanzania, where four of ten women have a lifetime exposure to physical or sexual violence by their male partners. To be able to suggest relevant and feasible community and health care based interventions, we explored community members' understanding and their responses to intimate partner violence. Methods A qualitative study using focus group discussions with 75 men and women was conducted in a community setting of urban Tanzania. We analysed data using a grounded theory approach and relate our findings to the ecological framework of intimate partner violence. Results The analysis resulted in one core category, "Moving from frustration to questioning traditional gender norms", that denoted a community in transition where the effects of intimate partner violence had started to fuel a wish for change. At the societal level, the category "Justified as part of male prestige" illustrates how masculinity prevails to justify violence. At the community level, the category "Viewed as discreditable and unfair" indicates community recognition of intimate partner violence as a human rights concern. At the relationship level, the category "Results in emotional entrapment" shows the shame and self-blame that is often the result of a violent relationship. At the individual level, the risk factors for intimate partner violence were primarily associated with male characteristics; the category "Fed up with passivity" emerged as an indication that community members also acknowledge their own responsibility for change in actions. Conclusions Prevailing gender norms in Tanzania accept women's subordination and justify male violence towards women. At the individual level, an increasing openness makes it possible for women to report, ask for help, and become proactive in suggesting preventive measures. At the community level, there is an increased willingness to intervene but further consciousness-raising of the human rights perspective of violence, as well as actively engaging men. At the macro level, preventive efforts must be prioritized through re-enforcement of legal rights, and provision of adequate medical and social welfare services for both survivors and perpetrators.